Unusual effect of temperature on direct fluorination of high temperature vulcanized silicone rubber and properties of the fluorinated surface layers - An, Zhenlian; Shan, Fangting; Yang, Long; Shen, Ruochen; Gu, Xiaoxiao; Zheng, Feihu; Zhang, Yewen (IEEE transactions on dielectrics and electrical insulation, 2018)
In order to investigate the effects of fluorination temperature on surface layer characteristics (chemical composition and structure, morphology, and thickness) and surface layer properties, high temperature vulcanized silicone rubber samples were fluorinated in a laboratory vessel using a F 2 /N 2 mixture with 12.5% F 2 by volume, at 0.1 MPa and the different temperatures of 25, 55, and 85 °C, for the same time of 30 min. ATR-IR analysis indicates that the substitution of fluorine atoms for hydrogen atoms of methyl groups is dominant for the fluorination at the different temperatures, while a substitution for methyl groups cannot be excluded. SEM cross-section and surface images show the fluorinated layers with nanostructured surfaces. The surface layer fluorinated at 55 °C appears to have the lowest degree of fluorination, but it clearly has the largest thickness and surface nanostructure size among the fluorinated layers. This unusual phenomenon is caused by two competing effects, the thermal activation of the substitution reaction and fluorine diffusion through the surface layer and the steric hindrance by the fluorinated methyl groups to the fluorination and fluorine diffusion. Contact angle measurements reveal that the fluorinated surfaces have high hydrophobicity and oleophobicity and thus an extremely low surface energy. Surface potential decay measurements show a much more rapid decay of potential on the fluorinated samples, compared to the unfluorinated sample. There is no significant difference in surface hydrophobicity or surface conduction between the fluorinated samples, due to the combined effect of compositional and structural changes. The difference in surface oleophobicity between the fluorination at 55 °C and the fluorination at 25 or 85 °C provides further evidence for the difference in their surface chemistry, because surface geometry of the fluorinated samples has little effect on the oleophobicity.